The role of pancreatic polypeptide in the regulation of energy homeostasis. (15th December 2015) - Khandekar, Neeta; Berning, Britt A.; Sainsbury, Amanda; Lin, Shu
Abstract: Imbalances in normal regulation of food intake can cause obesity and related disorders. Inadequate therapies for such disorders necessitate better understanding of mechanisms that regulate energy homeostasis. Pancreatic polypeptide (PP), a robust anorexigenic hormone, effectively modulates food intake and energy homeostasis, thus potentially aiding anti-obesity therapeutics. Intra-gastric and intra-intestinal infusion of nutrients stimulate PP secretion from the gastrointestinal tract, leading to vagal stimulation that mediates complex actions via the neuropeptide Y4 receptor in arcuate nucleus of the hypothalamus, subsequently activating key hypothalamic nuclei and dorsal vagal complex of the brainstem to influence energy homeostasis and body composition. Novel studies indicate affinity of PP for the relatively underexplored neuropeptide y6 receptor, mediating actions via the suprachiasmatic nucleus and pathways involving vasoactive intestinal polypeptide and insulin like growth factor 1. This review highlights detailed mechanisms by which PP mediates its actions on energy balance through various areas in the brain. Highlights: Pancreatic polypeptide in food intake & energy homeostasis. It's mechanisms of actions. Its potential in anti-obesity treatments.